Alcohol consumption. A leading risk factor for cancer. (1st November 2020) - Rehm, Jürgen; Shield, Kevin D.; Weiderpass, Elisabete
Abstract: In 2016, alcohol consumption was one of the leading risk factors for cancer development and cancer death globally, causing an estimated 376 200 cancer deaths, representing 4.2% of all cancer deaths, and 10.3 million cancer disability-adjusted life years lost, representing 4.2% of all cancer disability-adjusted life years lost. The impact of alcohol consumption on cancer in 2016 varied by age group; the proportion of cancer deaths attributable to alcohol consumption ranged from 13.9% of cancer deaths among people aged 30–34 years to 2.7% of cancer deaths among people aged 80–84 years. The burden of cancers caused by alcohol consumption might be decreased through (i) individual-level and societal-level interventions that reduce alcohol consumption, and (ii) measures that target those risk factors that interact with alcohol consumption to increase the risk of cancer or that directly affect the risk of alcohol-related cancers.